Cmentarzysko okrętów cennym obiektem przyrodniczym = A ship graveyard as natural sanctuary - Łotysz, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
After the WWI, the US navy had several hundreds of redundant transport ships, mainly wooden hulk steamers. In 1925 they were transferred to Mallows Bay on Potomac River, 30 miles south of Washington, DC, and ordered to be burned down. Some unburned remains of the hulks have been disfiguring the bay since.
Keywords: renaturalizacja; dziedzictwo poprzemysłowe; architektura krajobrazu; reclaiming by nature; landscape architecture; river; industrial heritage